Single-Site Heterogeneous Catalysts for Olefin Polymerization Enabled by Cation Exchange in a Metal-Organic Framework - Comito, Robert J; Fritzsching, Keith J; Sundell, Benjamin J; Schmidt-Rohr, Klaus; Dincă, Mircea (Journal of the American Chemical Society, 2016)
The manufacture of advanced polyolefins has been critically enabled by the development of single-site heterogeneous catalysts. Metal-organic frameworks (MOFs) show great potential as heterogeneous catalysts that may be designed and tuned on the molecular level. In this work, exchange of zinc ions in Zn5Cl4(BTDD)3, H2BTDD = bis(1H-1,2,3-triazolo[4,5-b],[4′,5′-i])dibenzo[1,4]dioxin) (MFU-4l) with reactive metals serves to establish a general platform for selective olefin polymerization in a high surface area solid promising for industrial catalysis. Characterization of polyethylene produced by these materials demonstrates both molecular and morphological control. Notably, reactivity approaches single-site catalysis, as evidenced by low polydispersity indices, and good molecular weight control. We further show that these new catalysts copolymerize ethylene and propylene. Uniform growth of the polymer around the catalyst particles provides a mechanism for controlling the polymer morphology, a relevant metric for continuous flow processes.